Mycobacterial Antibody Levels and Immune Restoration Disease in HIV Patients Treated in South East Asia - Sumatoh, Hermi R; Oliver, Benjamin G; Kumar, Manoj; Elliott, Julian H; Vonthanak, Saphonn; Vun, Mean Chhi; Singh, Sarman; Agarwal, Upasna; Kumar, Amitabh; Tan, Hong Yien; Kamarulzaman, Adeeba; Yunihastuti, Evy; et al. (Biomarkers in medicine, 2011)
Immune restoration disease (IRD) associated with Mycobacterium tuberculosis parallels the reconstitution of a pathogen-specific Th1 response. However, it is not clear whether humoral responses to M. tuberculosis antigens also rise, or whether antibody levels predict IRD. Here, humoral immunity to M. tuberculosis antigens was investigated in four Asian cohorts. Plasma samples were obtained from longitudinal prospective studies of HIV patients beginning antiretroviral therapy (ART) in New Delhi (India), Kuala Lumpur (Malaysia), Jakarta (Indonesia) and Phnom Penh (Cambodia). IgG antibodies to purified protein derivative, lipoarabinomannan and 38-kDa antigens of M. tuberculosis were quantitated using in-house ELISAs. IRD was defined as exacerbated symptoms of tuberculosis in patients on anti-tuberculosis therapy or a novel presentation of tuberculosis on ART. Pre-ART IgG levels to purified protein derivative, lipoarabinomannan and 38-kDa antigen were similar in the IRD and control groups from each site. Compared with non-IRD controls, a higher proportion of IRD patients had elevated IgG levels to lipoarabinomannan (defined as a greater than twofold increase) over 12 weeks of ART. However, this trend was not significant for the other antigens and longitudinal analyses did not reveal clear rises in antibody levels at the time of IRD. Levels of antibody to mycobacterial antigens do not predict IRD, but levels of antibody reactive with lipoarabinomannan rise during an IRD in some patients.